1981
DOI: 10.1177/00220345810600061401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diluent Monomer on the Physical Properties of Bis-GMA-based Composites

Abstract: The nature of the bis-GMA diluent present in composite formulations greatly affects such properties of the cured resin as setting time, strength, water sorption, and coefficient of thermal expansion. J Dent Res 60(6):983-989, June 1981 Introduction.Composite resins comprise the majority of anterior dental restorations. These materials have many desirable properties; however, their overall performance (in particular, their finishing, wear resistance, adaptation to cavity walls, color and storage stability, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…Composed of a high concentration of hydrophobic monomers, such as Bis-GMA (Table 1), Pre-Bond adhesive resin may create a hybrid layer with a high concentration of hydrophobic monomers and, consequently, lower hydrophilicity, [14][15][16] thus improving its mechanical properties. [17][18] Moreover, dual-curing mechanisms within the hybrid layer may have contributed to the higher µTBS when Pre-Bond resin infiltrated the primed dentin surface. Considering that All Bond 2 Primer A contains a tertiary amine as a component for the self-curing reaction, 12 and Pre-Bond resin has benzoyl peroxide, it is possible that free-radicals within the hybrid layer might have been created not only from light activation, but also from the self-curing redox reaction.…”
Section: Fractured Specimen Using All Bond 2 When Primer Was Light mentioning
confidence: 99%
“…Composed of a high concentration of hydrophobic monomers, such as Bis-GMA (Table 1), Pre-Bond adhesive resin may create a hybrid layer with a high concentration of hydrophobic monomers and, consequently, lower hydrophilicity, [14][15][16] thus improving its mechanical properties. [17][18] Moreover, dual-curing mechanisms within the hybrid layer may have contributed to the higher µTBS when Pre-Bond resin infiltrated the primed dentin surface. Considering that All Bond 2 Primer A contains a tertiary amine as a component for the self-curing reaction, 12 and Pre-Bond resin has benzoyl peroxide, it is possible that free-radicals within the hybrid layer might have been created not only from light activation, but also from the self-curing redox reaction.…”
Section: Fractured Specimen Using All Bond 2 When Primer Was Light mentioning
confidence: 99%
“…Due to its high viscosity, the Bis-GMA is usually diluted with triethylene glycol dimethacrylate (TEGDMA) [2]. However, TEGDMA has been linked to increased water sorption and polymerization shrinkage [2][3][4]. In order to overcome the drawbacks of the dilution process using TEGDMA, ethoxylated bisphenol A glycol dimethacrylate (Bis-EMA) has been investigated as an alternative monomer [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…10 It also has been reported that mechanical properties of crosslinked polymer prepared with polyfunctional monomers were influenced by the properties of reactive groups, including chain length and rigidity. [11][12][13][14][15][16][17] The results indicated that cross-linked polymers, having a short and rigid chain between double bonds, exhibited lower impact strength.…”
Section: Introductionmentioning
confidence: 99%